Climate justice for the southwestern coastal region of Bangladesh - Ashrafuzzaman, Md; Gomes, Carla; Guerra, João (Frontiers in Climate, 2022)
Climate change is seemed to be a moral, ethical and social justice issue, which makes it different from other development issues. The topmost instance of lack of justice of climate change is that the worst impacted are the ones who in the first place (such as SWCRB) had the lowest level of contribution to the greenhouse gas emissions and climate change is principally triggered by the industry-rich and business concerns spreading. The study employed the mixed method, combining qualitative and quantitative methods of data collection and analysis. Data and information collected from both primary and secondary sources. Regarding primary sources, quantitative data were collected from climate vulnerable community households using a structured questionnaire. On the other hand, FGD, IDI, KII, workshop, case study, and etc. This study explored the perceptions of people in the southwestern coastal region of Bangladesh (SWCRB), which is currently experiencing devastating effects of CCSLR including extreme natural disasters, changed seasonality, flooding, salinization, riverbed erosion, and waterlogging. These climate-induced changes are causing people of this area to lose their homes, livelihoods, and land, in addition to their lack of access to proper nutrition, fresh water, and healthcare which is protuberant to social injustices. A capability-based approach to climate justice is supported by this paper, which allows for people of this region to prepare and rebuild their own communities and create adaptive mechanisms based on their specific capabilities. This approach requires compensation (funding) from the global community, in addition to organizational connection between local people and other stakeholders. Based on the perception of people in the SWCRB, they are calling for community-based disaster management and inclusion in the discussion. Pervasive issues that these communities require include are sustainable development of embankments and infrastructure, as well as affordable and sustainable access to fresh water. Not only do industrialized nations need to provide this compensation for climate change, but they also must act quickly to reduce greenhouse gas emissions to zero and adapt to renewable energies to avoid worst-case scenario situations of climate change.